O discurso do fotojornalismo independente na guerra do Iraque - Furtado, Orleães Alan Mendonça (Universidade do Vale do Rio do Sinos, 2008)
this work investigates the independent photojournalism produced during Iraq War (2003), taking as objects of analysis the photographic book Unembedded: four independent photojournalists on the war in Iraq (2005). The main objective of this investigation is understood what a book can address to a reader in a war that received a huge coverage in the mainstream media. The progress of the research is based in three ways: the examination of the photographic book while a communicative process (a specific practice in photojournalism), an examination of the independent correspondents during the war and a specific analysis of the book’s discourse. The study is theoretically and methodologically based in four central authors: the Semiotics studies of Roland Barthes and Umberto Eco about the photography and the visual communication; the analysis of the photojournalism in John Tagg (establish through the Michel Foucault’s perspective); and the studies about Sociology of Violence in John Keane. It realized that the book U
Keywords: discurso; fotojornalismo independente; guerra do Iraque; fotojornalismo; discourse; Iraq War; photographic book; photojournalism; Ciências Sociais Aplicadas